2013
DOI: 10.1038/npp.2013.293
|View full text |Cite
|
Sign up to set email alerts
|

Fine Mapping on Chromosome 13q32–34 and Brain Expression Analysis Implicates MYO16 in Schizophrenia

Abstract: We previously reported linkage of schizophrenia and schizoaffective disorder to 13q32-34 in the European descent Afrikaner population from South Africa. The nature of genetic variation underlying linkage peaks in psychiatric disorders remains largely unknown and both rare and common variants may be contributing. Here, we examine the contribution of common variants located under the 13q32-34 linkage region. We used densely spaced SNPs to fine map the linkage peak region using both a discovery sample of 415 fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 48 publications
0
25
0
3
Order By: Relevance
“…MYO16 is expressed predominantly in hippocampal neurons to regulate synaptic cytoskeleton in neurocognitive developmental disorders (Liu et al, 2015). Previous evidence suggested that common variants within the MYO16 gene contribute to the genetic liability of schizophrenia (Rodriguez-Murillo et al, 2014). It is known that schizophrenia and BP might share some common pathophysiology (Konopaske et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MYO16 is expressed predominantly in hippocampal neurons to regulate synaptic cytoskeleton in neurocognitive developmental disorders (Liu et al, 2015). Previous evidence suggested that common variants within the MYO16 gene contribute to the genetic liability of schizophrenia (Rodriguez-Murillo et al, 2014). It is known that schizophrenia and BP might share some common pathophysiology (Konopaske et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, large scale genome-wide association (GWA) studies are commonly employed in the last decade to search susceptibility loci for complex human traits (McCarthy et al, 2008). Several GWA studies have identified many loci for the risk of developing BP (The Wellcome Trust Case Control Consortium, 2007; Baum et al, 2008; Ferreira et al, 2008; Sklar et al, 2008; Lee et al, 2011; Kuo et al, 2014; Muhleisen et al, 2014; Xu et al, 2014); however, conclusive and replicated findings are relatively scattered. Some examples are the ANK3 and CACNA1C genes (Ferreira et al, 2008; Muhleisen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, a naturally occurring F145S mutation in the FGF14 gene is implicated in the development of spinocerebellar ataxia 27 (SCA27), a severe motor and cognitive neurodegenerative disorder (Laezza et al, 2009; Brusse et al, 2006; Wozniak et al, 2007; Coebergh et al, 2014), and SNPs in the Fgf14 gene have been associated with depression and schizophrenia (Hsu et al, 2014; Verbeek et al, 2012; Rodriguez-Murillo et al, 2014; Di Re et al, 2017). Recent transcriptomics studies from human post-mortem brains identify FGF14 as a new schizophrenia risk gene, a finding that is corroborated by fgf14 −/− mice which exhibit phenotypes including changes in network activity, decreased gamma frequency, and cognitive impairments that mimic the human disease (Alshammari et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…In searching for PPI surfaces that could lead to the development of probes and drug-like molecules targeting Nav channels, we have identified FGF14, a member of the iFGF family, as a physiologically relevant accessory protein with implications for brain function and pathology in both animal models and humans (46 -48). FGF14 is an emerging diseaserelevant protein that was initially associated with neurological disorders such as ataxia (49) and, from more recent genomewide association studies (GWAS), as a potential risk factor for schizophrenia (47) and depression (46). Binding of FGF14 to Nav1.1, Nav1.2, and Nav1.6 exerts powerful effects on Na ϩ currents, producing phenotypes that are Nav isoform-dependent and distinct from those associated with other iFGFs (39 -41, 50 -53).…”
mentioning
confidence: 99%